Report of a rare case and review of adult intestinal duplication at the opposite side of mesenteric margin - Huang, Zhi-Hao; Wan, Zi-Hao; Vikash, Vikash; Vikash, Sindhu; Jiang, Cong-Qing (São Paulo Medical Journal, 2018)
CONTEXT: To study the previously discovered clinical entity of adult intestinal duplication and its treatment, and propose an extension to its existing classification. CASE REPORT: We report the case of an adult male with abdominal pain, constipation and vomiting. This patient underwent surgical separation of adhesions, reduction of torsion and intestinal decompression. Postoperative pathological findings confirmed the rare diagnosis of intestinal duplication. CONCLUSION: Adult intestinal duplication is quite rare. Its clinical manifestations are nonspecific. From this finding of intestinal duplication originating at the opposite side of the mesenteric margin, a further extension of the existing anatomical classification is proposed.